Redmond (2002) Revisited: Have Standardized Behavioral Rating Scales Gotten Better at Accommodating for Overlapping Symptoms with Language Impairment? - Redmond, Sean M.; Hannig, Kirsten M.; Wilder, Amy (Seminars in Speech and Language, 2019)
Seventeen years ago, Redmond reviewed five standardized behavioral rating scales and identified several aspects of their design that made them prone to mischaracterize language impairments as socioemotional behavioral disorders. The purpose of this report is to provide an update and extension of the original audit. We consulted test manuals to evaluate: (1) representation of children with language impairments in their standardization samples; (2) presence of language, or academic items within their inventories; (3) accommodations for administering the measure to children with language impairments; and (4) procedures for identifying inordinately punitive ratings. Overlapping language and academic symptoms continued to be a problem across current behavioral rating scales. Improvements since Redmond occurred in the representation of children with language impairments in standardization samples and in procedures for identifying inordinately punitive ratings. We discuss implications for clinical assessment, research programs, and instrument development.
Keywords: differential diagnosis; specific language impairment; ADHD; behavioral rating scales; reliability and validity